1987
DOI: 10.1111/j.1442-200x.1987.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of 48, XXX, +18 Double Trisomy

Abstract: We report a case of double trisomy, 48, XXX, + 18 in a newborn female who had low set ears, prominent occiput, receding chin, overlapping fingers, structural heart disease and other malformations. These deformities are similar to the characteristic manifestations of trisomy 18 syndrome. She died on the 10th day. Autopsy revealed VSD, ASD, PDA, coarctation of the aorta, Meckel's diverticulum and cerebellar hypoplasia. Our case showed unilateral anomalies on the right side. These may help to suggest the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There was one interesting suggestion by Rosenfeld et al 119811 that patients with 48,XXX, + 18 had rightsided dominant anomalies. Imai et al [1987] summarized from previous reports that right-sided malformations were dominant in auricle, kidney, and hand. In our patient, ear anomalies were symmetric, while the extra palmar crease was present only on the right hand.…”
Section: Discussionmentioning
confidence: 99%
“…There was one interesting suggestion by Rosenfeld et al 119811 that patients with 48,XXX, + 18 had rightsided dominant anomalies. Imai et al [1987] summarized from previous reports that right-sided malformations were dominant in auricle, kidney, and hand. In our patient, ear anomalies were symmetric, while the extra palmar crease was present only on the right hand.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous occurrence of double trisomy involving chromosomes 18 and X is uncommon. The majority of affected cases have been reported in infancy (Uchida and Bowman, 1961;Uchida et al, 1962;Ricci and Borgatti, 1963;Haas and Lewis, 1966;Emberger et al, 1971;Madahar et al, 1974;Verma and Dosik, 1980;Rosenfeld et al, 1981;Sonoda et al, 1987;Imai et al, 1987;Jaruratanasirikul and Jinorose, 1994;Moore et al, 1994;Tsukahara et al, 1994). To our knowledge, there are very few reports (den Hollander et al, 1994;Hanna et al, 1996) concerning prenatal diagnosis of 48,XXX,+18, but the genetic mechanisms by which double trisomy arose were not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Uchida and Bowman [1961] reported the first double trisomy case 48,XXX, + 18. Since then, a total of 16 cases have been reported [Ricci and Borgatti, 1963; Haas and Lewis, 1966; Engel et al, 1967; Taylor, 1968; Emberger et al, 1971; Madahar et al, 1974; Verma and Dosik, 1980; Rosenfeld et al, 1981; Sonoda et al, 1985; Imai et al, 1987; Sonoda et al, 1987; Jaruratanasirikul and Jinorose, 1994; Moore et al, 1994; Tsukahara et al, 1994; Chen et al, 2000]. One of the patients was a mosaic [Engel et al, 1967].…”
Section: To the Editormentioning
confidence: 99%
“…Maternal origin of extra X and 18 was determined in one case by using the polymorphic DNA markers from chromosomes X and 18 [Chen et al, 2000]. Rosenfeld et al [1981] and Imai et al [1987], reviewing their case as well as five cases in the literature, observed that malformations in the hands, ears, and kidneys showed significantly higher frequency on the right side. Although the reasons for this phenomenon were not clear, they felt that right‐sided malformations might indicate the possibility of 48,XXX, + 18.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation